Countreis of the World : Pakistan - Jameel Haque; Edited by Brown, Katharine (Singapore Times Media Private Ltd., 2004)
Presents information on the geography, history, government, economy, people, social life and customs, and arts of Pakistan, an Islamic country in South Asia. Suggested level: intermediate, junior secondary.
Include Colour Illustration and Index
Keywords: Pakistan